The ALMaQUEST Survey. XIII. Understanding Radial Trends in Star Formation Quenching via the Relative Roles of Gas Availability and Star Formation Efficiency - Pan, Hsi-An; Lin, Lihwai; Ellison, Sara L.; Thorp, Mallory D.; Sánchez, Sebastián F.; Bluck, Asa F. L.; Belfiore, Francesco; Piotrowska, Joanna M.; Scudder, Jillian M.; Baker, William M. (The Astrophysical journal, 2024)
Star formation quenching is one of the key processes that shape the evolution of galaxies. In this study, we investigate the changes in molecular gas and star formation properties as galaxies transit from the star-forming main sequence to the passive regime. Our analysis reveals that as galaxies move away from the main sequence toward the green valley the radial profile of specific star formation rate surface density (Σ sSFR ) is suppressed compared with main-sequence galaxies out to a galactocentric radius of 1.5 R e (∼7 kpc for our sample). By combining radial profiles of gas fraction ( f gas ) and star formation efficiency (SFE), we can discern the underlying mechanism that determines Σ sSFR at different galactocentric radii. Analysis of relative contributions of f gas and SFE to Σ sSFR uncovers a diverse range of quenching modes. Star formation in approximately half of our quenching galaxies is primarily driven by a single mode (i.e., either f gas or SFE), or a combination of both. A collective analysis of all galaxies reveals that the reduction in star formation within the central regions ( R < 0.5 R e ) is primarily attributable to a decrease in SFE. Conversely, in the disk regions ( R > 0.5 R e ), both f gas and SFE contribute to the suppression of star formation. Our findings suggest that multiple quenching mechanisms may be at play in our sample galaxies, and even within a single galaxy. We also compare our observational outcomes with those from galaxy simulations and discuss the implications of our data.